The Risks and Macroeconomic Impacts of HIV/AIDS in the Middle East and North Africa : Why Waiting to Intervene Can Be Costly - Robalino, David A. (World Bank, Washington, DC, 2014)
The authors develop a model of optimal growth to assess the risks of an HIV/AIDS epidemic and the expected economic impact in nine countries in the Middle East and North Africa region-Algeria, Djibouti, Egypt, Iran, Jordan, Lebanon, Morocco, Tunisia, and Yemen. The model incorporates an HIV/AIDS diffusion component based on two transmission factors-sexual intercourse and exchange of infected needles among intravenous drug users. Given high levels of uncertainty on the model parameters that determine the dynamics of the epidemic and its economic impact, the authors explore large regions of the parameter space. The prevalence rates in year 2015 would be below 1 percent in 16 percent of the cases, while they would be above 3 percent in 50 percent of the cases. On average, GDP losses across countries for 2000-2025 could approximate 35 percent of today's GDP. In all countries it is possible to observe scenarios where losses surpass today's GDP. The authors quantify the impact of expanding condom use and access to clean needles for intravenous drug users. They show that these interventions act as an insurance policy that increases social welfare. They also show that delaying action for five years can cost, on average, the equivalent of six percentage points of today's GDP.